Comparison of toxicities between Vibrio fluvialis and Vibrio furnissii strains isolated from environmental samples - Jainab, Tahsina; Hasan, Sayeema; Manchur, Mohammed Abul; Yasmin, Mahmuda; Nessa, Jamalun; Ahsan, Chowdhury Rafiqul (Bangladesh Journal of Microbiology, 2022)
Gastrointestinal episodes associated with Vibrio species have been rising worldwide in the last few years. In this study, toxicities of two very well characterized V. fluvialis and V. furnissii strains, isolated from environmental samples, were used to investigate the comparative pathogenicity of these strains. The results showed that there is a positive relationship between toxin production as well as a high interspecies correlation. In the analysis of toxicity, both species showed positive results with close similarity in cell death on BHK-21 cell line and destruction of RBC, which were indicative of cytotoxic and hemolytic activity, respectively. Besides, molecular analysis showed the absence of ctx, tdh, trh, stx1 and stx2 genes. On the other hand, reduced fluid accumulation ratio in rabbit ileal loop assay and paralysis of hind legs of Swiss Albino mice were observed for V. furnissi strain, which indicates the differences in pathogenicity between the two species. Bangladesh J Microbiol, Volume 38, Number 2, December 2021, pp 73-77